Factors Affecting Stress Level of School Age Children During the Covid-19 Pandemic - Wijanarko Heru Pramono; Emilia Puspitasari Sugiyanto; Candra Hadi Prasetyo (Indonesian Journal of Global Health Research, 2021)
This study aims to determine the factors that influence academic stress during the COVID-19 pandemic. The method used is a quantitative method. With a cross-sectional approach. The analysis used is univariate analysis to describe the characteristics of the respondents, univariate analysis using multiple linear regression analysis. Respondents were school-aged children in grades 5 & 6 at Islamic Integrated Elementary School Azzahra Demak with a total of 69 students using the proportional sampling method. With the inclusion criteria for school age children level 5 and 6 (final year students). The results of the study found that there was a simultaneous relationship between 4 factors that influenced learning, including the density of learning, time constraints, social demands, and achievement demands, indicated by a sig value of 0.00 < 0.05.